Sistem Informasi Penilaian Kinerja Pegawai Menggunakan Metode Multi Attribute Utility Theory (MAUT) Pada Kantor BAPENDA Kabupaten Sinjiai - Maulana, Reza; Masyhur, Zulkarmaim; alimin, Alfian (Jurnal INSYPRO (Information System and Processing), 2022)
Performance evaluation is important for every institution or company. If the work of each employee can be evaluated in the performance evaluation. Attendance-based performance measurement is not enough to reflect good performance in an assessment that only relies on employee attendance. There are other aspects of assessment that must be applied to identify talented and qualified employees. The study was conducted at the Regional Revenue Agency Office of Sinjai Regency. This study aims to measure the performance of Non ASN/PNS employees, using the Multi Attribute Utility Theory Method. This type of research uses a qualitative research approach, while the data collection methods used are observation, interviews, literature studies and questionnaires. The system testing method used is black box testing and User Acceptance Testing (UAT). which exists. This is evidenced by based on a questionnaire consisting of 10 questions and 35 respondents, it can be concluded that the average index is 74.9%.